Importance of Spiritual Intelligence (SQ) and Spiritual Congruence (SC) : Factors that May Contribute to Individual's Attitude towards Purchasing Decision in Halal Cosmetic - Azreen Jihan Che Mohd Hashim; Rosidah Musa (Global Journals Inc. (USA), 2024)
This paper reviews the articles on how importance does an individual's spiritual intelligence (SQ) and spiritual congruence (SC) affect individual's attitude in making decision in purchasing product. When the person lives in a way that blends spirituality into his daily life, it will reflect their attitudes and behavior in making the best decision in his life and this allows its association with the rational cognitive processes like goal achievement and problem solving. Meanwhile SC is to examine the degree of match between how consumers actually see themselves in relation to product image. The paper examines the academic literature on construct as well as presents SQ and SC as a causal factor in the formation of the attitude and behaviors of the consumer. The phenomenon of SQ in the organization and workplace has received enormous attention from other scholars. The construct of SQ in individual perspective and developing measurement scale to explore the dimensionality of the concept has not been much explored. While SC is to examine the degree of match between how consumers actually see themselves in relation to Halal cosmetic product image. Thus, this study attempts to enrich the understanding the importance of SQ from the Islamic and western perspective, and SC of individual' attitude towards purchase Halal cosmetic among female Muslim in Malaysia.